IMPLEMENTASI METODE SAW, WP DAN TOPSIS DALAM MENENTUKAN KARYAWAN TERBAIK - Dimas Nugroho; Robby Jordan; Yoga Pratama; Perani Rosyani (CV. Multi Kreasi Media, 2023)
In a company it is important that determines the quality of the employees at work who participate in developing the company. Therefore with the existence of a decision support system. This decision support system aims to expand decision-making capabilities in processing data and information for the user. The choice of the SPK method for solving problems has a major impact on the results obtained. Lack of knowledge about the functions and benefits of the SPK method leads to poor decision making. The problem that is often encountered is the selection of the DSS method to be used to solve a problem. This study will use the SAW (Simple Additive Weighting Method), WP (Weighted Product) method, TOPSIS (Technique for Order Preference by Similarity to Ideal Solution). So that we know the results of these three methods, successful or not, so that the company can know the capabilities of these employees.